2008
DOI: 10.1128/aac.00538-08
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility Testing and Molecular Classification of Paecilomyces spp

Abstract: In vitro susceptibility profiles of 58 Paecilomyces clinical isolates are reported. Amphotericin B, itraconazole, and echinocandins showed poor activity against Paecilomyces lilacinus, while the new triazoles were active against it. Paecilomyces variotii exhibited a different susceptibility pattern, being susceptible to most antifungal agents apart from voriconazole and ravuconazole.Paecilomyces species are saprophytic filamentous fungi that are found worldwide in soil and as air and water contaminants (9, 13)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
64
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 16 publications
6
64
1
1
Order By: Relevance
“…This finding is also consistent with the susceptibility profile of our isolate. In contrast, P. variotii isolates were susceptible to amphotericin B, itraconazole, and echinocandins, but showed reduced susceptibility to voriconazole (5). Similar susceptibility results were reported by Gonzalez et al (11), where voriconazole, posaconazole, and ravuconazole demonstrated good in vitro activity against P. lilacinum.…”
supporting
confidence: 75%
See 2 more Smart Citations
“…This finding is also consistent with the susceptibility profile of our isolate. In contrast, P. variotii isolates were susceptible to amphotericin B, itraconazole, and echinocandins, but showed reduced susceptibility to voriconazole (5). Similar susceptibility results were reported by Gonzalez et al (11), where voriconazole, posaconazole, and ravuconazole demonstrated good in vitro activity against P. lilacinum.…”
supporting
confidence: 75%
“…Voriconazole and posaconazole were found to possess maximum activity, whereas amphotericin B was least active. Echinocandins have shown variable in vitro activity against P. lilacinum (5,8,29,38). Voriconazole, consistent with its in vitro activity against P. lilacinum, has been used successfully for treatment of several cases with different clinical manifestations, including the present case (6,10,18,21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro amphotericin B was active against clinical P. variotii isolates but not against P. lilacinus (8). Among the azoles, only itraconazole and posaconazole showed clinically relevant activity against P. variotii.…”
mentioning
confidence: 92%
“…Interestingly, the echinocandins, especially micafungin and anidulafungin, were highly active against P. variotii, with MIC values being as low as 0.016 mg/liter. Conversely, P. lilacinus was not inhibited by the echinocandins, underscoring the importance of correct species identification (8).…”
mentioning
confidence: 99%